(untitled) (Medico Legal Update, 2019)
This study is a descriptive study to assess the level of self-confidence in kindergartens in Babylon . The study sample included 50 children with (30) male and (20) female This study was conducted in the province of Babylon in the Mahaweel district – the Imam City in the kindergarten Masoudi for the semester 2016- 2017 , The sample collection period was extended from December 2016 to January 2017. Design of the study : Descriptive study , setting of the study : The study was conducted in the province of Babylon in the Mahaweel district , Time of the study : The Semester 2016 - 2017 , the sample of study : The sample was selected in Al-Masoudi kindergarten in Al-Imam district , The study consisted of (50) children, males (30) and females (20). The results of the study showed a difference in the level of self confidence in children through the results of questionnaires, which were based on four fields : motor skills, self-reliance, social skills and physical appearance and included the age of children and level of education for the father and mother.